2022
DOI: 10.1016/j.jmgm.2021.108042
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the non-covalent interaction between the PF-07321332 inhibitor and the SARS-CoV-2 main protease

Abstract: We have studied the non-covalent interaction between PF-07321332 and SARS-CoV2 main protease at the atomic level using a computational approach based on extensive molecular dynamics simulations with explicit solvent. PF-07321332, whose chemical structure has been recently disclosed, is a promising oral antiviral clinical candidate with well-established anti-SARS-CoV-2 activity in vitro. The drug, currently in phase III clinical trials in combination with ritonavir, relies on the electrophilic attack of a nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 53 publications
0
39
0
1
Order By: Relevance
“…The present study clarified that the relevant protonation state for the structural stability of the bound inhibitor differs from the ligands, illustrating the importance of evaluating the binding affinity for the appropriate protonation state. Procacci and co-workers carried out the classical MD simulations of SARS-CoV-2 M pro in the ligand-bound form with PF-07321332 for the IP and neutral states using two different kinds of force fields [25] . The authors found that the active-site protonation state and force fields have implications for the inhibitor-bound structure, highlighting the necessity of the QMD simulation in addition to the classical MD simulation based on empirical force fields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study clarified that the relevant protonation state for the structural stability of the bound inhibitor differs from the ligands, illustrating the importance of evaluating the binding affinity for the appropriate protonation state. Procacci and co-workers carried out the classical MD simulations of SARS-CoV-2 M pro in the ligand-bound form with PF-07321332 for the IP and neutral states using two different kinds of force fields [25] . The authors found that the active-site protonation state and force fields have implications for the inhibitor-bound structure, highlighting the necessity of the QMD simulation in addition to the classical MD simulation based on empirical force fields.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, docking and/or classical molecular dynamics (MD) simulations for M pro [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , starting from the crystal structures captured from X-ray crystallography, have been widely conducted to search for effective inhibitors by evaluating the affinity for the active site of M pro , mainly consisting of the catalytic dyad, i.e., Cys145 and His41 ( Figure 1 a ). As hydrogen/proton is not resolved in the usual X-ray crystallography due to the spatial resolution, the protonation states should be presumed in these simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nirmatrelvir has been observed to form tight conjugates with SARS-CoV-2 M pro [ 17 , 18 , 19 , 20 ]. Analysis of the structure of SARS-CoV-2 M pro in complex with nirmatrelvir shows that, in addition to the S-C covalent bond, nirmatrelvir is further stabilized through a network of hydrogen bonds and hydrophobic interactions, which further strengthens its binding to the active site of SARS-CoV-2 M pro [ 17 ].…”
Section: The Development Of Paxlovid™ (Nirmatrelvir/ritonavir)mentioning
confidence: 99%
“…Analysis of the structure of SARS-CoV-2 M pro in complex with nirmatrelvir shows that, in addition to the S-C covalent bond, nirmatrelvir is further stabilized through a network of hydrogen bonds and hydrophobic interactions, which further strengthens its binding to the active site of SARS-CoV-2 M pro [ 17 ]. Molecular dynamics simulations provide further support for the inhibitory mechanism of nirmatrelvir toward SARS-CoV-2 M pro , which occurs in two steps: an initial non-covalent addition with the dyad in a neutral form with the formation of the thiolate-imidazolium ion pair, and ligand relocation for finalizing the electrophilic attack [ 18 ]. Despite the presence of lopinavir or ritonavir, nirmatrelvir still exhibited a high binding ability to the active site of SARS-CoV-2 M pro [ 19 ].…”
Section: The Development Of Paxlovid™ (Nirmatrelvir/ritonavir)mentioning
confidence: 99%